2011
DOI: 10.1002/zoo.20336
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cycle approach by rectal temperature and fecal progesterone in a female killer whale, Orcinus orca

Abstract: This study aimed to validate the measurements of body temperature and fecal progesterone concentrations as minimally invasive techniques for assessing ovarian cycle in a single sexually mature female killer whale. Rectal temperature data, fecal and blood samples were collected in the dorsal position using routine husbandry training on a voluntary basis. The correlations between rectal temperature and plasma progesterone concentration and between fecal and plasma progesterone concentrations were investigated. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Faecal samples were collected from captive, female bottlenose dolphins of different reproductive states, and although the authors were able to establish a threshold value of progesterone metabolite values to confirm corpus luteum activity, few additional conclusions were achieved (Biancani et al 2009). In another study on a captive female killer whale, the authors demonstrated that faecal progesterone profiles were visually similar to plasma profiles; however, they could not show a significant statistical correlation between faecal and plasma concentrations of progesterone (Kusuda et al 2011).…”
Section: Faecesmentioning
confidence: 94%
See 1 more Smart Citation
“…Faecal samples were collected from captive, female bottlenose dolphins of different reproductive states, and although the authors were able to establish a threshold value of progesterone metabolite values to confirm corpus luteum activity, few additional conclusions were achieved (Biancani et al 2009). In another study on a captive female killer whale, the authors demonstrated that faecal progesterone profiles were visually similar to plasma profiles; however, they could not show a significant statistical correlation between faecal and plasma concentrations of progesterone (Kusuda et al 2011).…”
Section: Faecesmentioning
confidence: 94%
“…In another study on a captive female killer whale, the authors demonstrated that faecal progesterone profiles were visually similar to plasma profiles; however, they could not show a significant statistical correlation between faecal and plasma concentrations of progesterone (Kusuda et al. ).…”
Section: Biological Matricesmentioning
confidence: 99%
“…Killer whales have a diverse diet ranging from small schooling fish and squid to large baleen and sperm whales [54]. Kusuda et al [43] monitored the body temperature of a female killer whale over a course of more than a year and found that its body temperature changed cyclically from 35.3°C to 35.9°C, with an average of 35.5°C.…”
Section: Sample Materials and Methodsmentioning
confidence: 99%
“…(1)-the empirical equation established by Yoshida and Miyazaki[10]; and (2) using Eq. (2)-the phosphate-water oxygen isotope fractionation equation[58], assuming that body temperatures are 33.5°C for the sperm whale[44] and 35.5°C for all the other whales[41][42][43].The d18 O w values derived from the d18 O p values of our modern whale samples (with the exception of the killer whale) using Eq. (1) are mostly higher than the observed d18 O w values of modern Atlantic and Pacific Ocean waters…”
mentioning
confidence: 99%
“…The relationship between the production rates of pulsed call sequences for mothers and their body temperature, which is an indirect physiological indicator controlled by hormones, was also analyzed in parallel during the pre-parturition period to investigate the possibility that hormones cause the acoustic activity in mothers. For example, body temperature changes during the estrous cycle are positively correlated with progesterone levels in a female beluga (Katsumata et al 2006a) and a female killer whale (Kusuda et al 2011). The acrophases of diurnal rhythms in body temperature and cortisol levels were observed at approximately the same time in male Indo-Pacific bottlenose dolphins (Funasaka et al 2011).…”
mentioning
confidence: 99%